Homeobox Genes in Cancers: From Carcinogenesis to Recent Therapeutic Intervention - Feng, Yangyang; Zhang, Tongyue; Wang, Yijun; Xie, Meng; Ji, Xiaoyu; Luo, Xiangyuan; Huang, Wenjie; Xia, Limin (Frontiers in Oncology, 2021)
The homeobox (HOX) genes encoding an evolutionarily highly conserved family of homeodomain-containing transcriptional factors are essential for embryogenesis and tumorigenesis. HOX genes are involved in cell identity determination during early embryonic development and postnatal processes. The deregulation of HOX genes is closely associated with numerous human malignancies, highlighting the indispensable involvement in mortal cancer development. Since most HOX genes behave as oncogenes or tumor suppressors in human cancer, a better comprehension of their upstream regulators and downstream targets contributes to elucidating the function of HOX genes in cancer development. In addition, targeting HOX genes may imply therapeutic potential. Recently, novel therapies such as monoclonal antibodies targeting tyrosine receptor kinases, small molecular chemical inhibitors, and small interfering RNA strategies, are difficult to implement for targeting transcriptional factors on account of the dual function and pleiotropic nature of HOX genes-related molecular networks. This paper summarizes the current state of knowledge on the roles of HOX genes in human cancer and emphasizes the emerging importance of HOX genes as potential therapeutic targets to overcome the limitations of present cancer therapy.